PERSEPSI DAN MINAT SISWA SLBN WIRADESA PEKALONGAN MELANJUTKAN PENDIDIKAN DI PTKIN - Prayogi, Arditya; Katni Katni; Sigit Dwi Laksana; Delima; Yenti Apriyani (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Access to higher education for people with disabilities remains difficult for various reasons, including the requirement of "physically and mentally healthy" for those wishing to register for the Joint Selection for Entrance to State Universities (SBMPTN). This clearly limits people with disabilities from enrolling in certain study programs. This study aims to analyze the perceptions of students with disabilities regarding continuing higher education at universities and to analyze the demand for students with disabilities to continue their education at universities. This study uses a descriptive qualitative approach. The researcher serves as the key instrument. Data collection methods include in-depth interviews, observation, and documentation. Data analysis involves data reduction, data presentation, and conclusions. Data validity is checked through triangulation of sources and methods. The results show that students with disabilities have a positive perception of higher education, but this perception is still general and has not been specifically directed to PTKIN due to the lack of information and visual representation available in the school environment. Student interest in continuing to PTKIN is relatively high, especially for those who are suited to certain majors, but still face uncertainty due to limited information, career guidance, and independent readiness.